Effect of memory load on eye movement control: A study using the reading span test - Miyuki Azuma; Takehiro Minamoto; Ken Yaoi; Mariko Osaka; Naoyuki Osaka (Bern Open Publishing, 2014)
We investigated the effect of memory load on attentional control using the Reading Span Test (RST), a task that requires working memory capacity. Previous studies have shown that a shortage of working memory resources leads to a deficit of inhibition of taskirrelevant information and that memory load affects eye movement control. Here, we recorded eye movement and integrated it with RST performance. Total fixation time and the number of regressions showed a memory load effect with the to-be-remembered word, and RST performance was also affected under high memory load. We concluded that a shortage of working memory resources caused by memory load prevents flexible eye movement control and may cause a deficit in inhibitory control based on intrusion errors.